(a∧–b) ∨ (–b∧c) ∨ (–a∧c) = (a∧–b) ∨ (–a∧c)

How can I prove this,

I tried to use the distribution law for the first/last two terms, but it doesn't seem to work. Can anyone give me some hints?

Thanks a lot

Printable View

- Jan 10th 2010, 03:56 PMwxyjBoolean algebra Help
(a∧–b) ∨ (–b∧c) ∨ (–a∧c) = (a∧–b) ∨ (–a∧c)

How can I prove this,

I tried to use the distribution law for the first/last two terms, but it doesn't seem to work. Can anyone give me some hints?

Thanks a lot - Jan 10th 2010, 04:58 PMr0r0trog
i can't see the symbols... but an easy way to do it is to just make a truth table out of it. you only have 3 unknowns so you only have 8 different combinations to calculate.

- Jan 10th 2010, 05:53 PMwxyj
- Jan 10th 2010, 05:55 PMr0r0trog
well, as i said, i can't see your symbols... write them as AND, NAND, OR etc and i'll see what i can do.

- Jan 10th 2010, 07:05 PMwxyj
(a AND –b) OR (–b AND c) AND (–a AND c) = (a AND –b) OR (–a AND c)

Thanks for trying to help - Jan 10th 2010, 08:05 PMDrexel28
If you will remember the algebra of sets is Boolean isomorphic to sentence logic. So, this is equivalent to showing that

$\displaystyle \left(A\cap B'\right)\cup\left(B'\cap C\right)\cap\left(A'\cap C\right)=\left(A\cap B'\right)\cup\left(A'\cap C\right)$

The left side is $\displaystyle \left(A\cap B'\right)\cup\left(B'\cap C\right)=\left(A\cap\left(B'\cap C\right)\right)\cup\left(B'\cap\left(B'\cap C\right)\right)=\left(A\cap B'\cap C\right)\cup\left(B'\cap C\right)$$\displaystyle =B'\cap C$

So the left side is $\displaystyle \left(B'\cap C\right)\cap\left(A'\cap C\right)=B'\cap A'\cap C$ and the right side is $\displaystyle \left(A\cap B'\right)\cup\left(A'\cap C\right)=\left(A'\cup\left(A\cap B'\right)\right)\cap\left(\left(C\cup\left(A\cap B'\right)\right)\right)$ which equals $\displaystyle \left(\left(A'\cup A\right)\cap\left(A'\cap B'\right)\right)\cap\left(\left(C\cup A\right)\cap\left(C\cap B'\right)\right)=\left(A'\cap B'\right)\cap\left(C\cap A\cap B'\right)$ which gives...bleh. - Jan 10th 2010, 09:20 PMwxyj
- Jan 10th 2010, 09:23 PMDrexel28
- Jan 11th 2010, 01:51 AMemakarovQuote:

(a /\ -b) \/ (-b /\ c) \/ (-a /\ c) = (a /\ -b) \/ (-a /\ c)

Next, it's easy to see that the left-hand side is the right-hand side plus one disjunct: (-b /\ c). So we should show that adding this disjunct does not change anything. If we show that (a /\ -b) \/ (-a /\ c) = (-b /\ c) \/ X for some X, then

(a /\ -b) \/ (-b /\ c) \/ (-a /\ c) = (-b /\ c) \/ X \/ (-b /\ c) = (-b /\ c) \/ X = (a /\ -b) \/ (-a /\ c)

To show that (a /\ -b) \/ (-a /\ c) = (-b /\ c) \/ X, we can use the fact that the representation of a function as a DNF where each disjunct has all prop. letters is unique. So one has to add c to the first disjunct on the left and b to the second one, as well as a to the right-hand side. This can be done by adding c \/ -c, b \/ -b and a \/ -a and using the distributive law. - Jan 11th 2010, 11:43 AMwxyj
- Jan 11th 2010, 12:38 PMDrexel28
- Jan 11th 2010, 01:15 PMwxyj